Options for managing human threats to high seas biodiversity. (1st April 2020) - O'Leary, Bethan C.; Hoppit, George; Townley, Adam; Allen, Harriet L.; McIntyre, Christina J.; Roberts, Callum M.
Abstract: Areas beyond national jurisdiction (ABNJ) constitute 61% of the world's oceans and are collectively managed by countries under the United Nations Convention on the Law of the Sea (UNCLOS). Growing concern regarding the deteriorating state of the oceans and ineffective management of ABNJ has resulted in negotiations to develop an international legally binding instrument (ILBI) for the conservation and sustainable use of biodiversity beyond national jurisdiction under UNCLOS. To inform these negotiations, we identified existing and emerging human activities and influences that affect ABNJ and evaluated management options available to mitigate the most pervasive, with highest potential for impact and probability of emergence. The highest-ranking activities and influences that affect ABNJ were fishing/hunting, maritime shipping, climate change and its associated effects, land-based pollution and mineral exploitation. Management options are diverse and available through a variety of actors, although their actions are not always effective. Area-based management tools (ABMTs), including marine protected areas (MPAs), were the only consistently effective option to mitigate impacts across high-ranked activities and influences. However, addressing land-based pollution will require national action to prevent this at its source, and MPAs offer only a partial solution for climate change. A new ABNJ ILBI could help unify management options and actors to conserve marine biodiversity and ensure sustainable use. Incorporating a mechanism to establish effective ABMTs into the ILBI will help deliver multiple objectives based on the ecosystem approach. Highlights: UN negotiations are ongoing to protect marine life beyond national jurisdiction. We identify five key human threats to the high seas and evaluate management options. Key threats were: fishing; shipping; climate change; land-based pollution; mining. Only marine protected areas (MPAs) offered effective mitigation across most threats. A high seas agreement could unify management options and actors for sustainability.